Application of cosmetic nail varnish does not affect the antifungal efficacy of amorolfine 5% nail lacquer in the treatment of distal subungual toenail onychomycosis: results of a randomised active‐controlled study and in vitro assays. Issue 5 (11th February 2016) - Sigurgeirsson, B.; Ghannoum, M. A.; Osman‐Ponchet, H.; Kerrouche, N.; Sidou, F.
Summary: As onychomycosis is unsightly, this study clinically evaluated whether the antifungal efficacy of amorolfine 5% nail lacquer (NL) was affected by a masking, natural‐coloured, cosmetic nail varnish applied 24 h later; in vitro investigations were also performed. Subjects with mild‐to‐moderate distal subungual toenail onychomycosis were randomised to receive amorolfine 5% NL once weekly with or without cosmetic nail varnish applied 24 h later. After 12‐week treatment, antifungal activity of affected toenail clippings was assessed by measurement of zones of inhibition (ZOIs) on Trichophyton mentagrophytes seeded agar plates. Mean diameters were 53.5 mm for the amorolfine 5% NL‐alone group ( n = 23) and 53.6 mm for amorolfine 5% NL plus cosmetic nail varnish group ( n = 25). Also, mycological cultures of subungual debris at week 12 were negative for all subjects in both groups. Most subjects (88%) reported that cosmetic nail varnish masked their infected toenails. Additionally, cadaver human nails coated in vitro with or without cosmetic nail varnish 10 min or 24 h post amorolfine NL application all gave ZOIs on Trichophyton rubrum agar plates representing potent antifungal activity. In conclusion, cosmetic nail varnish applied post amorolfine had no effect on the subungual antifungal activity of amorolfine 5% NL or its penetration through toenails.